Usability of Amorphous Manganese Oxide for Assessing the Proteoglycan Content in Articular Cartilage - Korpi, Riikka M.; Ahola, Susanna; Behrouz, Gamzegul; Lammentausta, Eveliina; Karhula, Sakari S.; Saarakkala, Simo; Rieppo, Lassi; Finnilä, Mikko; Stapf, Siegfried; Rosenholm, Jessica; Blanco Sequieros, Roberto; Nieminen, Miika T.; et al. (Wiley, 2026)
Osteoarthritis (OA) is a highly common chronic disease that decreases functional capacity and can cause disability. The early detection of the disease could help to develop treatments that may reduce the progression if not cure the disease. Proteoglycan depletion is known to occur at an early state of OA and the delayed gadolinium-enhanced magnetic resonance imaging (MRI) of cartilage (dGEMRIC) is currently considered as one of the most accurate methods for analyzing the depletion in articular cartilage (AC) despite the toxicity-related issues with gadolinium contrast agents. The aim of this study was to investigate the usability of amorphous manganese oxide (MnOx) for assessing the proteoglycan content in AC. The relaxation times of MnOx were determined at various fields and compared with the effect of gadolinium-diethylene triamine pentaacetic acid (Gd-DTPA) at 7.1 T. The diffusion of MnOx and Gd-DTPA into AC was analyzed ex vivo and followed for 24 h. Cartilage degeneration was evaluated with two histological scoring systems (OARSI and Mankin) to assess the relationship between OA severity and MnOx concentration. Relaxivity of MnOx was high and diffusion to the AC was faster than that of Gd-DTPA at 7.1 T. Using MnOx, T1 followed histological optical density (OD) of stained proteoglycans and correspondingly the concentration profiles followed in reverse the OD profiles in each human sample in a similar manner to Gd-DTPA in dGEMRIC. This pilot study showed some preliminary superiority in relaxation and diffusion into AC of MnOx in relation to Gd-DTPA.